Are bacterial communities and aggregation in fragile soils influenced by the management system? - Tiago Paula da Silva; Caio Simões dos Santos Nicolau; Carlos Wagner Ribeiro Junqueira; Gustavo Souza Lima Sant’Anna; Everaldo Zonta; Nivaldo Schultz; Irene da Silva Coelho; Marcos Gervasio Pereira (Farming System)
Light-textured soils are widely distributed globally and, despite their limitations, have been integrated into agricultural production systems. This study aimed to assess how management systems—conventional tillage (CT) and no-till (NT)—affect aggregate formation pathways (physicogenic and biogenic) and bacterial communities. Two management systems (NT and CT) and three cover crops were evaluated: CJ: Crotalária (Crotalaria juncea (40 ​kg ​ha−1); M: Millet (Pennisetum glaucum - 60 ​kg ​ha−1); and C: Cocktail (Crotalária - Crotalaria juncea - 10 ​kg ​ha−1, Jack bean - Canavalia ensiformis - 75 ​kg ​ha−1, and Millet - Pennisetum glaucum - 30 ​kg ​ha−1). Undisturbed soil samples were collected from the crop row at a depth of 0.00–0.10 ​m. Aggregates with diameters between 9.7 and 8.0 ​mm were classified as biogenic or physicogenic. In addition to the chemical attributes of the aggregates, total organic carbon (TOC) and its fractions (mineral-associated organic carbon, MAOC; particulate organic carbon, POC; and free light fraction carbon, FLFC) were quantified. The structure and bacterial composition of the aggregates were also characterized. A higher proportion of biogenic aggregates (53–64%) was observed compared to physicogenic aggregates (36–47%). Cover crops exhibited significant differences in pH, calcium (Ca2+), base saturation, phosphorous (P), and percentage of base saturation. The management systems differed significantly for Ca2+ and P, with CT showing higher values than NT. The management system influenced organic matter accumulation and stabilization in the aggregates, with MAOC content being significantly lower in CT. POC and TOC were also significantly lower in physicogenic aggregates under CT. Bacterial community richness, diversity, and structure were significantly influenced by the management system, with greater richness and diversity in NT compared to CT. Network analysis revealed NT had more nodes and edges (65 and 406, respectively) than CT (52 and 357, respectively. Phyla abundance differed between the systems, with Firmicutes and Entotheonellaeota more abundant in CT, while WPS_2, GAL15, Bdellovibrionota, and Myxococcota were more abundant in NT. Despite the relatively short period of NT implementation (5 years), it had a positive effect on the bacterial community, which may subsequently influence nutrient and carbon content and their fractions in the aggregates.